Dietary cholesterol reduces blood pressure and alters lipid profiles in stroke-prone spontaneously hypertensive rats - Yutaro Nishikata; Kenjiro Tatematsu; Yoshiaki Saito; Toshiyuki Matsunaga; Naoki Ohara (PLoS ONE, 2026)
Although cholesterol (Chol) is widely recognized as a risk factor for cardiovascular disease, dietary Chol intake has been reported to extend the lifespan of stroke-prone spontaneously hypertensive rats (SHRSP). The mechanisms responsible for this paradoxical effect remain unclear. The present study examined changes in organ lipid profiles and associated molecular factors in SHRSP rats fed a Chol-enriched diet. Four-week-old male SHRSP/Izm rats were assigned to three groups and fed ad libitum for 12 weeks with either a control diet (Ctr), a diet supplemented with 1% w/w Chol (Chol), or a diet containing 1% w/w Chol plus 0.025% w/w lovastatin to suppress endogenous Chol synthesis. Systolic blood pressure was measured before and after the feeding period, and tissues were collected for analyses of sterol content, fatty acid composition, prostaglandin E 2 (PGE 2 ) levels, and renal histopathology. Relative to the Ctr group, the Chol group exhibited a significant 9–10% reduction in systolic blood pressure. This reduction was accompanied by pronounced alterations in lipid profiles, including changes in phytosterol content and decreased arachidonic acid ratios in serum and kidney. There was a downward trend in hepatic PGE 2 levels, and a similar tendency was observed in the kidney. Comparable changes in lipid profiles were observed in the Chol + lovastatin group. Histological analysis revealed modest attenuation of renal pathological features in Chol-fed rats. This study demonstrates for the first time that dietary Chol reduces renal phytosterol accumulation and suppresses the AA-PGE 2 axis, changes that coincide with a 9–10% reduction in systolic blood pressure and attenuated glomerular inflammation. These integrated findings provide a mechanistic framework linking dietary Chol to the previously reported lifespan extension in this stroke-prone model. Although these changes may contribute to improved renal pathology, further studies are required to clarify causal relationships.